A new species of troglobitic crab of the genus Stygothelphusa Ng, 1989, from Sarawak, Malaysia (Crustacea: Decapoda: Brachyura: Gecarcinucidae) - Ng, Peter K. L.; Grinang, Jongkar (Zootaxa, 2014)
A new species of cave crab, Stygothelphusa antu new species, is described from limestone formations in Temurang, Sarawak, Malaysia. The new species is the most highly adapted to a cavericolous lifestyle among the four known species of Stygothelphusa, having a pale body pigmentation, reduced eyes and elongated pereopods. In contrast, the other three species have normal eyes that almost completely fill the orbits. The new species also differs from its congeners by a number of carapace, pereopod and gonopod characters.